Phenylboronic acid-based amphiphilic glycopolymeric nanocarriers for in vivo insulin delivery. Issue 18 (18th April 2016) - Guo, Honglei; Li, Hongmei; Gao, Juntao; Zhao, Guangxi; Ling, Lilu; Wang, Bin; Guo, Qianqian; Gu, Yong; Li, Chaoxing
Abstract : Diabetes mellitus, a disorder of glucose regulation, is a global burden affecting millions of people across the world. Abstract : Diabetes mellitus, a disorder of glucose regulation, is a global burden affecting millions of people across the world. Oral delivery offers a comfortable and physiologically acceptable way to administer insulin to diabetic patients. However, insulin is a protein, which tends to be degraded by enzymes at the gastrointestinal level and shows low bioavailability via an oral route. Here, to investigate a system that is capable of protecting insulin from being damaged and consistently delivering insulin in response to glucose level changes, we prepared amphiphilic glycopolymer poly(d -gluconamidoethyl methacrylate-random-3-acrylamidophenylboronic acid) (p(GAMA- r -AAPBA)), and the glycopolymer assembled into nanoparticles with a narrow size distribution. Insulin was efficiently encapsulated into nanoparticles with a loading capacity up to 11%. An insulin release experiment revealed that the insulin release could be controlled by modifying the composition of glycopolymers and changing the glucose medium. Cell viability showed that p(GAMA- r -AAPBA) nanoparticles had good cytocompatibility. Moreover, a 2-deoxy-[3 H ]d -glucose (2-DOG) uptake measurement indicated that insulin-loaded nanoparticles had the same physiological function as insulin. A western blot analysis and an immunofluorescence assay revealed that compared to conventional insulin, insulin released from nanoparticles has an identical hypoglycemic mechanism that increased the translocation of glucose transporter type 4 (Glut4) to the plasma membrane. Importantly, there was a significant decrease in blood glucose levels after the oral administration of insulin-loaded p(GAMA- r -AAPBA) nanoparticles to diabetic rats. Therefore, p(GAMA- r -AAPBA) nanoparticles have the potential to be applied as an oral delivery system for proteins and peptides.